2011
DOI: 10.1126/science.1198542
|View full text |Cite
|
Sign up to set email alerts
|

A Dynamic Knockout Reveals That Conformational Fluctuations Influence the Chemical Step of Enzyme Catalysis

Abstract: Conformational dynamics play a key role in enzyme catalysis. While protein motions have clear implications for ligand flux, a role for dynamics in the chemical step of enzyme catalysis has not been clearly established. We generated a mutant of E. coli dihydrofolate reductase (DHFR) that abrogates millisecond time scale fluctuations in the enzyme active site without perturbing its structural and electrostatic preorganization. Remarkably, this dynamic knockout severely impairs hydride transfer. Thus we have foun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
599
2
5

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 443 publications
(619 citation statements)
references
References 26 publications
13
599
2
5
Order By: Relevance
“…The theoretical and experimental framework outlined above has been used extensively to detect motions on the μs-to-ms time scale within proteins and understand their function (Beach et al 2005;Bhabha et al 2011;Boehr et al 2006b;Eisenmesser et al 2005;Farber et al 2012;Korzhnev et al 2010Korzhnev et al , 2004Kovermann & Balbach, 2013;Mulder et al 2001a;Saio et al 2014;Sugase et al 2007;Whittier et al 2013;Zeeb & Balbach, 2005). Some notable examples of its use are discussed in detail in Section 5.…”
Section: Relaxation Dispersionmentioning
confidence: 99%
“…The theoretical and experimental framework outlined above has been used extensively to detect motions on the μs-to-ms time scale within proteins and understand their function (Beach et al 2005;Bhabha et al 2011;Boehr et al 2006b;Eisenmesser et al 2005;Farber et al 2012;Korzhnev et al 2010Korzhnev et al , 2004Kovermann & Balbach, 2013;Mulder et al 2001a;Saio et al 2014;Sugase et al 2007;Whittier et al 2013;Zeeb & Balbach, 2005). Some notable examples of its use are discussed in detail in Section 5.…”
Section: Relaxation Dispersionmentioning
confidence: 99%
“…56 Another high profile work that has attempted to support the dynamical proposal and to challenge the catalytic preorganization idea has studied the effect of mutations that restrict the protein conformational changes. 40 In particular, this work argued that the mutational induced reduction in catalysis is due to dynamical effects, and also that the reorganization change upon mutation is very small and thus presumably not responsible for this change in catalysis (based on inspecting the observed structural changes upon mutation). However, our subsequent simulation study 73 has shown that the observed catalysis simply reflects the alternation of the free energy surface, and the corresponding changes in preorganization.…”
Section: B Experimental Studies With Direct Theoretical Analysesmentioning
confidence: 99%
“…Although serious concerns have been raised about this proposal, [23][24][25][26][27][28][29] it remains popular and articles in its defense continue to be published in leading journals. 20,[30][31][32][33][34][35][36][37][38][39][40][41][42] In order to explore the dynamical proposal, we have to recognize that in contrast to some recent works, that argued that our attempts to address the dynamical proposal just leads to confusion in the field, 43 it is in fact quite simple to address this issue in a completely rigorous scientific way. To achieve this, it is imperative to avoid semantic confusion and use very clear definitions of what is meant by dynamical proposals.…”
Section: Introductionmentioning
confidence: 99%
“…4) and slower time scales 5,31,32 and are often attributed to conformational (classical) distributions of the D-A distance 4,5,7,[33][34][35] . Other approaches 12,27,36 factor out and quantize the D-A vibration (~100 fs), as well as the much higher frequency (~10 fs) vibrational mode of the tunneling particle, which is a common feature in all analytical models (see Supplementary Discussion 4).…”
Section: Deep Tunneling Modelsmentioning
confidence: 99%
“…Proton transport (PT) in biological systems has been the subject of many studies, both experimental [1][2][3][4][5][6] and theoretical [7][8][9][10][11][12] . A better understanding of this phenomenon is sought because it underpins so many fundamental life processes [13][14][15][16][17][18] .…”
mentioning
confidence: 99%